Techniques For Managing A Broadcast Media Business with Management Principles - Winda Kustiawan; Siti Nuraisah Nst; Rindiyani Rindiyani; Nadia Maharani; Mhd Farhan Aziz; Muhammad Fatur Rizki (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
This study examines the application of management principles in the operation of broadcasting media businesses in an era where information flows are rapidly expanding. Effective management in the processes of news coverage and broadcasting is essential to ensure that the information delivered to the public remains accurate, relevant, and highly credible. The purpose of this research is to explore how management principles can be utilized to improve the operational quality of broadcasting media and enhance the institutions’ ability to respond to industry dynamics.The method used is a qualitative approach through a literature study, critically reviewing various primary and secondary sources. The findings indicate that the proper implementation of management principles can strengthen work structures, improve team coordination, and maximize the efficiency of broadcasting processes. These results provide new insights into management strategies that enable broadcasting media to adapt to contemporary needs and challenges. Furthermore, the study underscores the importance of continuous managerial innovation to maintain the competitiveness of broadcasting institutions amid technological changes and the evolving preferences of audiences.